From terminal ileitis to Crohn's disease: how capsule endoscopy is crucial to diagnosis. Issue 5 (17th September 2020) - Freitas, Marta; Cúrdia Gonçalves, Tiago; Boal Carvalho, Pedro; Dias de Castro, Francisca; Rosa, Bruno; João Moreira, Maria; Cotter, José
Abstract : Background and aims: Terminal ileitis is a common condition and may be associated with a wide variety of diseases, mostly Crohn's disease. Although small bowel capsule endoscopy (SBCE) is a valuable diagnostic tool for small-bowel diseases, data regarding its diagnostic impact on isolated terminal ileitis are sparse. The aim of this study was to evaluate the diagnostic value of SBCE for isolated terminal ileitis detected during ileocolonoscopy and to assess predictive factors for Crohn's disease diagnosis. Methods: This is a retrospective study including consecutive patients undergoing SBCE after diagnosis of terminal ileitis without colonic mucosal abnormalities on ileocolonoscopy between January 2016 and September 2019. Results: This included 102 patients with isolated terminal ileitis on ileocolonoscopy. Positive findings on SBCE were found in 82.4% of patients. After performing SBCE, 61.8% of patients had a final diagnosis, being Crohn's disease the most common (34.3%), followed by NSAIDs enteropathy (12.7%). Extraintestinal manifestations ( P = 0.003), weight loss ( P = 0.02), abnormal imaging ( P = 0.04) and positive SBCE findings ( P = 0.001) were independently associated with Crohn's disease diagnosis. Regarding SBCE, presence of proximal small-bowel disease ( P = 0.02), diffuse findings ( P = 0.002) and moderate to severe inflammatory activity (Lewis score ≥ 790) ( P < 0.001) were independently associated with Crohn's disease diagnosis. Conclusion: SBCE is a valuable tool that should be systematically used in patients with isolated terminal ileitis on ileocolonoscopy, since it revealed a high diagnostic yield, supporting a definite diagnosis in almost two-thirds of patients, and Crohn's disease diagnosis in approximately one-third of patients. A diagnosis of Crohn's disease should be considered when a patient with terminal ileitis on ileocolonoscopy shows proximal involvement, diffuse findings and/or moderate to severe inflammatory activity on SBCE.